2018
DOI: 10.5897/jvmah2017.0558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk analysis of bovine brucellosis in Asella organized dairy farm, Oromia Regional State, South East Ethiopia

Abstract: A cross-sectional study was conducted on organized Dairy Farm at Asella, Oromia Regional State of Ethiopia to determine seroprevalence and risk analysis of bovine brucellosis in May, 2016. A total of 304 samples were collected; all were tested and confirmed serologically using Rose Bengal plate test (RBPT) and complement fixation test (CFT). Out of 304 samples tested, overall seroprevalence of RBPT and CFT results was12.48% (38) and 9.87% (30) respectively, which was higher in animals above two years age than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
5
1
Order By: Relevance
“…In the other hand, the present finding was lower than the previous research works conducted in different parts of Ethiopia by Abay [37] in Arsi, Gebawo et al [38] in Adami Tullu, Hunduma and Regassa [21] in East Shoa Zone, Hailu et al [39] in Jig-Jiga zone of Somali Regional State, Gebreyohans [40] in Addis Ababa, Tariku [41] in Chafa State Dairy Farm, Taye [42] in Abernosa Cattle Breeding Ranch, and Mussie et al (2007) [43] in Bahir Dar milk shed who reported magnitude of 4.9%, 4.3%, 4.1%, 1.38%, 1.5%, 22%, 19.5%, and 4.63%, respectively. Moreover, the present finding was by far much lower than the findings of Wossene et al [44] (14.6%), Eyob et al [45] (9.87%), Mekonnen et al [46] (6.1%), Alehegn et al [47] (4.9%), Gelma et al [48] (4.7%), Hika et al [49] (3.75%), Berhe et al [50] (3.19%), Megersa et al [51] (3.5%), Kemal and Minda [52] (4.95%), Jergefa et al [22] (2.9%), Hagos et al [53] (2.4%), Fekadu et al [54] (2%), Dinknesh et al [55] (1.04%), Moti et al [56] (1.97%), Yohannes et al [57] (2.6%), Abera et al [58] (2.7%), Bulcha et al [59] (1.04%) and Yitagele et al [60] (1.3%) who reported in Jikow District (Gambella), Asella, Western Tigray, Gondar Town, Borana Zone, Bishoftu Town, Tigray, Southern and Eastern Ethiopia, Agarfa and Berbere Districts of Bale Zone, Central Oromiya, Alage district, Eastern Showa, Becho District, Guto-Gida district, Arsi Zone, Hawassa Town, Adama Town and Eastern Ethiopia, respectively.…”
Section: Discussioncontrasting
confidence: 94%
“…In the other hand, the present finding was lower than the previous research works conducted in different parts of Ethiopia by Abay [37] in Arsi, Gebawo et al [38] in Adami Tullu, Hunduma and Regassa [21] in East Shoa Zone, Hailu et al [39] in Jig-Jiga zone of Somali Regional State, Gebreyohans [40] in Addis Ababa, Tariku [41] in Chafa State Dairy Farm, Taye [42] in Abernosa Cattle Breeding Ranch, and Mussie et al (2007) [43] in Bahir Dar milk shed who reported magnitude of 4.9%, 4.3%, 4.1%, 1.38%, 1.5%, 22%, 19.5%, and 4.63%, respectively. Moreover, the present finding was by far much lower than the findings of Wossene et al [44] (14.6%), Eyob et al [45] (9.87%), Mekonnen et al [46] (6.1%), Alehegn et al [47] (4.9%), Gelma et al [48] (4.7%), Hika et al [49] (3.75%), Berhe et al [50] (3.19%), Megersa et al [51] (3.5%), Kemal and Minda [52] (4.95%), Jergefa et al [22] (2.9%), Hagos et al [53] (2.4%), Fekadu et al [54] (2%), Dinknesh et al [55] (1.04%), Moti et al [56] (1.97%), Yohannes et al [57] (2.6%), Abera et al [58] (2.7%), Bulcha et al [59] (1.04%) and Yitagele et al [60] (1.3%) who reported in Jikow District (Gambella), Asella, Western Tigray, Gondar Town, Borana Zone, Bishoftu Town, Tigray, Southern and Eastern Ethiopia, Agarfa and Berbere Districts of Bale Zone, Central Oromiya, Alage district, Eastern Showa, Becho District, Guto-Gida district, Arsi Zone, Hawassa Town, Adama Town and Eastern Ethiopia, respectively.…”
Section: Discussioncontrasting
confidence: 94%
“…48,49 This could be explained by the fact that these two factors are the typical outcome of the brucellosis. 31,41,49 Other studies have also shown a significant association between the disease and abortion and retained fetal. 27,41,43,50 Similarly, studies from different African countries show that brucellosis in bovine directly correlates with the presence of abortion.…”
Section: Discussionmentioning
confidence: 96%
“…On the other side, lower seroprevalence was recorded in different parts of Ethiopia, 11 with 0.73% in Jimma Zone, 24 0.49% in Western Shewa, 25 0.4% in urban dairy farms of Northern Ethiopia, 26 0.2% in Debrebirhan and Ambo Towns, 12 and with 0.05% in Arsi Zone. There are reports of a higher seroprevalence rate of bovine brucellosis in other parts of the country, 27 3.1% in Jimma Zone of Oromia region, 28 2.77% in the Addis Ababa dairy cattle, 29 4.3% in Adami Tulu, central Ethiopia, 30 4.9% in Western Tigray, 3 8.0% in pastoral region of the country, 31 9.87% in Asella organized dairy farm, 32 10.6% in Borana, 33 11.0% in Wuchale-Jida district, central Ethiopia, 34 and with 11.2% in pastoral and agro-pastoral areas of East Shewa Zone. Similarly, higher seroprevalence was reported in other African countries 35 with 5.3% in Tanzania, 36 24.0% in Nigeria, 37 21.9% in Ghana 38 and 24.5% in Sudan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations